1998
DOI: 10.1021/ic980843f
|View full text |Cite
|
Sign up to set email alerts
|

Chirality-Controlling Chelate (CCC) Ligands in Analogues of Platinum Anticancer Agents. Influence of N9 Substituents of Guanine Derivatives (G) on the Distribution of Chiral Conformers of (CCC)PtG2with CCC =N,N-Dimethyl-2,3-diaminobutane

Abstract: Chirality-controlling chelate (CCC) ligands are a class of chiral diamine ligands with one or two chiral secondary amine ligating groups. Analogues of platinum anticancer agents containing CCC ligands exhibit unusual steric and dynamic features. In this study NMR and CD methods were used to evaluate the influence of the N9 substituent in guanine derivatives (G) on conformer distribution in one class of (CCC)PtG(2)() complexes. We employed the CCC ligand, N,N'-dimethyl-2,3-diaminobutane [Me(2)()DAB with S,R,R,S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
276
0

Year Published

2003
2003
2007
2007

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 55 publications
(298 citation statements)
references
References 56 publications
22
276
0
Order By: Relevance
“…Common CD features of previously studied cis-[PtA 2 G 2 ] adducts (G = detached guanine-base derivatives) allowed us to establish that the HT conformers make the greatest contribution to the CD spectrum [54,57,59,60] and that HT conformers of opposite chirality (L or D) also have opposite CD features. Moreover, the CD spectrum of a mixture of conformers is reflective of the dominant conformer in solution.…”
Section: Resultsmentioning
confidence: 97%
“…Common CD features of previously studied cis-[PtA 2 G 2 ] adducts (G = detached guanine-base derivatives) allowed us to establish that the HT conformers make the greatest contribution to the CD spectrum [54,57,59,60] and that HT conformers of opposite chirality (L or D) also have opposite CD features. Moreover, the CD spectrum of a mixture of conformers is reflective of the dominant conformer in solution.…”
Section: Resultsmentioning
confidence: 97%
“…[11,12,16,17] This dominance was attributed to interligand interactions, which were classified as "first-to-first," "first-to-second," and "second-to-second" sphere com- munications. [17,18] The latter two types of interactions involve phosphate groups, [11,12,17,18] and in this study we examine adducts lacking this group in order to focus on firstto-first sphere communications (FFC). FFC are interligand interactions involving portions of the ligands close to the metal center.…”
Section: Introductionmentioning
confidence: 99%
“…[9,14,15] Studies with [Pt{(S,R,R,S)-Me 2 dab}G 2 ] and [Pt{(R,S,S,R)-Me 2 dab}G 2 ] complexes (Me 2 DAB = N,N'-dimethyl-2,3-diaminobutane, and has four asymmetric centers at the N, C, C, and N chelate ring atoms) demonstrated a correlation between the sign of the CD signal and the chirality of the major HT form. [14,15] HT conformers have a head-to-tail orientation of the guanine bases and can have either a D or L chirality depending upon the handedness of two straight lines; one passes through the platinum center perpendicularly to the coordination plane, and the other connects the O6 atoms of the two guanines. [16,17] Furthermore, studies with the related [Pt{(S,R,R,S)-bip}G 2 ] and [Pt{(R,S,S,R)-bip}G 2 ] complexes (BIP = 2,2'-bipiperidine) indicated that a mixture of 25 % DHT, 50 % HH, and 25 % LHT essentially had a CD spectrum that lacked any intensity.…”
Section: Introductionmentioning
confidence: 99%